Katerina - Frey, James, 1969- (New York, NY : Scout Press, an imprint of Simon & Schuster, Inc., 2018)
"Katerina...is a sweeping love story alternating between 1992 Paris and Los Angeles in 2018. At its center are a young writer and a young model on the verge of fame, both reckless, impulsive, addicted, and deeply in love. Twenty-five years later, the writer is rich, famous, and numb, and he wants to drive his car into a tree, when he receives an anonymous message that draws him back to the life, and possibly the love, he abandoned years prior."--
Keywords: Authors -- Fiction; FICTION / Literary; FICTION / Coming of Age; FICTION / General; Authors; Bildungsromans; Models (Persons) -- Fiction; Authors -- Fiction; Paris (France) -- Fiction; Los Angeles (California) -- Fiction; California -- Los Angeles; France -- Paris; Romance fiction; Bildungsromans; Fiction; Romance fiction; Psychological fiction; Bildungsromans